E-Modul Materi Biogas Untuk Pendidikan Vokasi Agribisnis Ternak Ruminansia - Kartika Kusuma Ariani; L.R Retno Susanti; Adeng Slamet (JKTP: Jurnal Kajian Teknologi Pendidikan, 2021)
Development of E-Modules on Agribusiness Subjects for Ruminant Livestock Breeding Biogas at SMK Negeri 1 Gelumbang to produce valid, practical and effective products. Rowntree's development model is used to guide which contains three stages, namely planning, writing preparation, and writing and editing. The third stage is also called the evaluation stage using Tessmer's formative evaluation (self evaluation, expert review, one to one, small group, and field test). The subject of the research was the class XII students of Ruminant Livestock Agribusiness at SMK Negeri 1 Gelumbang. Collecting data using observation techniques, interviews, walkthroughs, questionnaires and tests. The results of research on the validity of the E-Modul by three validators obtained an average of 86.67% so that it is categorized as very valid. The results of the practicality test of E-Modules in all groups obtained an average of 83.81% in the one to one stage and 87.14% in the small group stage with a very practical category. The results of the E-Modul effectiveness test on student learning outcomes with an N-gain mean value of 0.77 in the high category. The conclusion that the resulting e-Module is valid, practical and effective.AbstrakPengembangan E-Modul pada Mata Pelajaran Agribisnis Pembibitan Ternak Ruminansia Materi Biogas di SMK Negeri 1 Gelumbang untuk menghasilkan produk yang valid,praktis dan efektif. Model pengembangan Rowntree digunakan untuk memandu yang berisi tiga tahap, yaitu perencanaan, persiapan penulisan, dan penulisan dan penyuntingan. Tahap ketiga disebut juga dengan tahap evaluasi menggunakan evaluasi formatif Tessmer (self evaluation, expert review, one to one, small group, dan field test).  Subjek penelitian adalah siswa kelas XII Agribisnis Ternak Ruminansia SMK Negeri 1 Gelumbang. Pengumpulan data menggunakan teknik observasi, wawancara, walkthrough, angket dan tes. Hasil penelitian terhadap validitas E-Modul oleh tiga orang validator didapatkan rerata 86,67 % sehingga dikategorikan sangat valid.  Hasil uji kepraktisan E-Modul pada semua kelompok diperoleh rerata  sebesar 83,81% pada tahap one to one dan 87,14 % pada tahap small group dengan kategori sangat praktis. Hasil uji efektivitas E-Modul terhadap hasil belajar siswa dengan nilai rerata N-gain sebesar 0,77 dengan kategori tinggi. Kesimpulan bahwa e-Modul yang dihasilkan valid, praktis dan efektif.